Multipoint Problem for Nonisotropic Partial Differential Equations with Constant Coefficients - Ptashnik, B. I.; Symotyuk, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We investigate the well-posedness of a problem with multipoint conditions with respect to a chosen variable t and periodic conditions with respect to coordinates x 1,..., x p for a nonisotropic (concerning differentiation with respect to t and x 1,..., x p) partial differential equation with constant complex coefficients. We establish conditions for the existence and uniqueness of a solution of this problem and prove metric theorems on lower bounds for small denominators appearing in the course of the construction of its solution.